Assessing the Satisfaction and Acceptability of an Online Parent Coaching Intervention: A Mixed-Methods Approach - Qu, Lu; Chen, Huiying; Miller, Haylie; Miller, Alison; Colombi, Costanza; Chen, Weiyun; Ulrich, Dale A. (Frontiers in Psychology, 2022)
Background Parent-mediated intervention (PMI) has been studied in promoting skill acquisition or behavior change in the children with autism spectrum disorder. Most studies emphasize on the improvement of child’s core symptoms or maladaptive behaviors, making parental perceived competence and self-efficacy secondary. Yet, the evaluations of intervention implementation are under-reported, especially when translating such interventions into a new population or context. This research investigated the intervention implementation of a 12-week parent coaching intervention which was delivered through telehealth and tailored to Chinese population. The intervention was based on the Parent-mediated Early Start Denver Model with culturally adapted lectures, manuals, and demonstration and commentary videos. This study aimed to evaluate the intervention implementation by assessing parents’ satisfaction, acceptability, appropriateness, and feasibility. Method A randomized controlled trial was conducted with two telehealth conditions: self-directed and web+group therapy. Parents in the self-directed condition received intervention individually through the online learning platform. The web+group therapy condition navigated the same program with weekly 1.5-h group coaching sessions via videoconferencing. This mixed-methods study used a concurrent convergent design to evaluate the intervention implementation at post-intervention. The quantitative data was collected from the Program Evaluation Survey and the qualitative data was collected from five focus groups. Results Parents in self-directed group reported significantly lower scores in total perceived competence than parents in web+group therapy condition, while there was no group difference on the total self-efficacy. Tailored feedback, demonstration and commentary videos, peer commenting, live coaching, and guided reflection were the top-five acceptable telehealth strategies that were strongly endorsed by parents. Family centered care, home-based intervention, strategies relative to daily activities, the remote learning platform, and the program-based community were elements that parents considered when evaluating the program’s appropriateness. Parent modeling, step-by-step instructions, and tailored feedback were key components in making intervention strategies feasible for parents to implement at home. Conclusion Findings indicate the application of telehealth was acceptable, appropriate, and feasible for Chinese parents. Group-based parent coaching intervention via videoconferencing could be a promising home-based service model to increase parental perceived competence. A large-scale RCT is needed to investigate the effectiveness of group-based PMI via telehealth.